An apparatus and method for electromagnetically synergistic in-situ catalytic degradation and capture of SF6 waste gas.

CN122722085BActive Publication Date: 2026-10-16WUHAN INST OF TECH +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611181702.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-08-05
Publication Date
2026-10-16
Estimated Expiration
2046-08-05

AI Technical Summary

Technical Problem

该结构带来难以同步解决的三项技术缺陷:固相催化剂远离微波电磁场,仅依靠高温尾气导热受热,微波非热催化作用无法利用,系统能量利用效率不足35%;若将吸波催化填料直接装填进波导强电场,材料受热后介电损耗急剧增大,短时间局部超温超1600℃产生热奔烧结,同时电磁极化造成微波全反射、阻抗失衡,极易烧毁磁控管,形成业内不能在波导内置填料的技术偏见;氟硫自由基在催化剂表面快速生成CaF2致密阻隔层,仅依靠自然热扩散难以穿透钝化层,催化剂深层活性组分无法参与反应,填料有效利用率普遍低于40%,设备长期运行降解效率下滑严重,频繁停工更换耗材

Benefits of technology

架构创新,微波能量利用率大幅提升:摒弃波导放电 + 后置固定床分体结构,石英放电管的多功能复合催化材料内置在微波强电场区,微波电磁场同时作用气相裂解与固相催化界面,微波综合能量利用率由传统<35% 提升至 65% 以上;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122722085B_ABST
    Figure CN122722085B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of catalytic degradation, and particularly relates to a device and method for capturing and degrading SF6 waste gas by electromagnetic synergistic in-situ catalytic degradation. The device comprises a gas distribution system and an arc-catalytic reaction system. The arc-catalytic reaction system comprises a microwave source, a three-screw tuner, a rectangular waveguide, and a quartz discharge tube crossing the rectangular waveguide. The quartz discharge tube is filled with multifunctional composite catalytic material in the tube segment of the internal strong electric field of the rectangular waveguide. The multifunctional composite catalytic material is SiC foam ceramic with a catalytic film wrapped on the surface. The composite active catalytic film comprises transition metal oxides and alkaline earth metal oxides. The complex dielectric constant and open-topological structure of the SiC foam ceramic are designed to match the received microwave, so that the core area and the edge of the SiC foam ceramic simultaneously excite diffuse micro-arc and generate high temperature. In the present application, the microwave comprehensive energy utilization rate and the multifunctional composite catalytic material utilization rate are improved, and the tail gas is free of greenhouse gas emission.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of catalytic degradation technology, and in particular to an apparatus and method for electromagnetically synergistic in-situ catalytic degradation and capture of SF6 waste gas. Background Technology

[0002] Sulfur hexafluoride (SF6) is widely used in high-voltage switches, GIS and other power equipment due to its excellent insulation and arc-quenching properties. However, SF6 has a greenhouse effect potential 25,200 times that of carbon dioxide and a natural atmospheric lifetime of up to 3,200 years, leading many countries to include it in their key greenhouse gas control programs. With the increasing volume of power grid maintenance and the dismantling of old electrical equipment, the emission of waste SF6 continues to rise. Traditional incineration and liquid-phase hydrolysis methods have drawbacks such as highly toxic byproducts, large volumes of wastewater, and high treatment costs. Atmospheric pressure microwave plasma treatment technology, due to its simple process and lack of secondary wastewater pollution, is gradually becoming the mainstream technology for the harmless disposal of SF6.

[0003] Currently, all industrially applied microwave plasma treatment solutions adopt a two-stage, spatially separated architecture of discharge cracking and solid-phase trapping. The plasma discharge zone is located inside the waveguide, while the fixed bed of CaO, MgO, and other solid fluorine particles is placed outside the downstream field of the reactor. This structure brings three technical defects that are difficult to solve simultaneously: the solid catalyst is far from the microwave electromagnetic field and relies solely on the high-temperature exhaust gas for heat conduction, making it impossible to utilize the non-thermal catalytic effect of microwaves, resulting in a system energy utilization efficiency of less than 35%; if the microwave-absorbing catalyst filler is directly packed into the strong electric field of the waveguide, the dielectric loss of the material increases sharply after heating, causing local overheating exceeding 1600°C in a short time, resulting in thermal runaway sintering. At the same time, electromagnetic polarization causes total microwave reflection and impedance imbalance, which can easily burn out the magnetron, leading to a technical prejudice in the industry against embedding fillers in the waveguide; fluorine and sulfur free radicals rapidly generate a dense CaF2 barrier layer on the catalyst surface, which cannot penetrate the passivation layer by natural thermal diffusion alone, preventing the deep active components of the catalyst from participating in the reaction, resulting in an effective utilization rate of fillers generally below 40%, and a severe decline in equipment degradation efficiency during long-term operation, leading to frequent shutdowns and replacement of consumables.

[0004] Based on the above situation, the industry urgently needs to develop a new integrated in-situ processing technology to simultaneously overcome three major technical bottlenecks: impedance mismatch, high-temperature thermal runaway, and product lattice passivation. Summary of the Invention

[0005] The purpose of this invention is to address the aforementioned shortcomings of the prior art by proposing an electromagnetically synergistic in-situ catalytic degradation and capture device and method for SF6 waste gas.

[0006] The primary objective of this invention is to provide an electromagnetically synergistic in-situ catalytic degradation and capture device for SF6 waste gas, comprising a gas distribution system and an electric arc-catalytic reaction system; The arc-catalytic reaction system includes a microwave source, a three-screw tuner, a rectangular waveguide, and a quartz discharge tube that runs through the rectangular waveguide. The quartz discharge tube is filled with a multifunctional composite catalytic material within a section of the rectangular waveguide that is located in a strong electric field. The outlet of the gas distribution system is connected to one end of the quartz discharge tube. The microwaves generated by the microwave source are introduced into the rectangular waveguide by a three-screw tuner. The multifunctional composite catalytic material is a SiC foam ceramic with a composite active catalytic film coated on its surface; The composite active catalytic film comprises transition metal oxides and alkaline earth metal oxides; The complex permittivity and open-cell topology of the SiC foam ceramic are designed to match the microwaves it receives, so that the core region and the edge of the SiC foam ceramic can simultaneously generate diffuse micro-arcs and produce high temperatures.

[0007] Furthermore, the three-dimensional open-cell topology of the SiC foam ceramic is designed to be integrated with the rectangular waveguide TE 10 Microwave-based natural electromagnetic impedance matching is achieved; the SiC foam ceramic has a three-dimensional open-cell topology with a porosity of 85%–93%, an open-cell diameter of 15–25 PPI, and a bulk density of 0.25–0.40 g / cm³. 3 This parameter system enables multi-level scattering and focusing of electromagnetic waves, while the gas bed pressure drop is ≤5kPa, avoiding gas backflow under high flow rate conditions.

[0008] Furthermore, the diameter of the quartz discharge tube is 40-50 mm, and the complex permittivity of the SiC foam ceramic has a real part ε′ = 8-15 and an imaginary part ε″ = 2-6. The incident microwaves are not significantly reflected and deeply coupled into the interior of the multifunctional composite catalytic material; the contact points of the micropores in the multifunctional composite catalytic material generate a geometric electric field polarization distortion of ≥10² times, spontaneously igniting a transient localized micro-arc that is diffusely distributed throughout the entire domain.

[0009] By controlling the imaginary part ε'' between 2 and 6, at 2.45 GHz, this range ensures that the microwave penetration depth is precisely within a few centimeters. This spatially matches the limited diameter of the quartz discharge tube, allowing microwave energy to penetrate extremely uniformly into the SiC framework at the center of the tube, simultaneously exciting diffuse micro-arcs in both the core and the edges. Controlling the real part ε' between 8 and 15 limits the electromagnetic impedance jump at the interface to a tunable range. Combined with a three-screw tuner at the waveguide front end, the reflected power can be easily reduced to near zero (reflectivity <1.5%) through destructive interference. If ε' > 15, the impedance drops drastically, and the three-screw tuner will lose its tuning capability at 2.45 GHz, resulting in direct total reflection of the microwaves.

[0010] Furthermore, in the multifunctional composite catalytic material, the loading of transition metal oxides and alkaline earth metal oxides is 10% to 25%.

[0011] Furthermore, the transition metal oxide is Fe2O3 or CuO, and the alkaline earth metal oxide includes CaO and MgO. The mass ratio of the transition metal oxide to the alkaline earth metal oxide is 1-2:8-9.

[0012] Furthermore, the composite active catalytic film also includes rare earth oxides, with a loading of 0.5% to 3%.

[0013] Furthermore, the preparation method of the multifunctional composite catalytic material is as follows: the transition metal salt and alkaline earth metal salt are dissolved in a solvent with a complexing agent and stirred in a water bath to obtain a precursor sol; the SiC foam ceramic is immersed in the above precursor sol and then taken out and the ceramic channels are blown open. Then the SiC foam ceramic is allowed to stand and gel at a certain temperature and then calcined under a nitrogen protective atmosphere.

[0014] Furthermore, the complexing agent is citric acid, the water bath temperature is 60-70℃, the SiC foam ceramic is gelled at 100℃ for 12 hours, heated to 750℃ at a heating rate of 5℃ / min under a nitrogen protective atmosphere, and calcined at that temperature for 3 hours.

[0015] Furthermore, the precursor sol also includes 0.5% to 3% rare earth oxides by mass fraction.

[0016] Furthermore, the gas distribution system is used to precisely proportion SF6 waste gas and auxiliary gas source with a specific C / F molar ratio of 1:2 to 1:6 or an H / F molar ratio of 1:1 to 2:1, to prepare the mixed waste gas to be treated and quantitatively deliver it to the electric arc-catalytic reaction system.

[0017] The second objective of this invention is to provide a method for electromagnetically synergistic in-situ catalytic degradation and capture of SF6 waste gas, using the aforementioned apparatus, with the following specific steps: Start the gas distribution system and use high-purity nitrogen or argon as the purging gas to pressurize and purge the inside of the quartz discharge tube. Start the gas distribution system and pass the prepared mixed waste gas containing SF6 into the quartz discharge tube; When the microwave source is turned on, continuous microwaves are injected into the rectangular waveguide. Fluorine / sulfur ions are converted into solid inorganic salts in situ under the action of the multifunctional composite catalytic material and solidified and accumulated on the porous walls of the multifunctional composite catalytic material.

[0018] This invention mixes SF6 waste gas with a reducing auxiliary gas containing water vapor, and introduces it into a quartz discharge tube at a set flow rate and molar ratio, injecting continuous microwaves of 2.45 GHz into a rectangular waveguide. The specific reaction process is as follows: Electromagnetic impedance matching and micro-area ignition: Electromagnetic waves penetrate the quartz discharge tube wall without reflection and are fully coupled into the deep layer of SiC foam ceramic; Under the action of electromagnetic loss, the macroscopic lattice temperature of SiC foam ceramic rapidly rises to the catalytic activity window of 700℃~850℃ within 100 s, and at the same time, a large number of local gas phase micro-area electric arcs are ignited within the microsecond-level transient window of the contact points inside the porous network. Arc-catalytic in-situ complete pyrolysis of gas phase: The mixed gas flows through the three-dimensional through-holes of the multifunctional composite catalytic material in the direction of gravity or in the direction of gravity. Under the dense bombardment of high-energy electrons (average electron energy 6-12 eV) in the micro-area arc, the highly electronegative SF6 molecules undergo stepwise dissociation of sulfur-fluorine bonds (SF bonds) before contacting the wall, forming highly reactive F• free radicals, S• free radicals and low-fluoride sulfur free radicals. In-situ electro-migration and solidification driven by a high-frequency alternating electric field: The fragmented free radicals flow towards the surface of the active catalyst layer and initially react with the exposed CaO / MgO active sites, forming an initial CaF2 / MgSO4 product layer on the outer surface of the catalyst layer. As the reaction continues, the CaF2 / MgSO4 product layer lattice accumulates and becomes denser, forming a dense passivation barrier on the catalyst layer surface that hinders further conventional thermal diffusion of free radicals. At this point, a high-frequency micro-alternating electric field (electric field strength ≥ 10) is established at the solid-gas interface by a localized micro-arc and alternating microwave field. 5 Driven by this non-thermoelectric field force (V / m), lattice defect polarization and electro-migration are forced to occur within the dense product layer. This drives the fluorine / sulfur ions in the outer layer to overcome the lattice mismatch barrier, accelerate their penetration through the lattice voids of the already formed dense product layer, and continuously migrate to the deeper layers of the catalyst layer. There, they continuously undergo spontaneous gas-solid mineralization reactions with the newly formed CaO / MgO interface, achieving in-situ continuous transformation and solidification of solid inorganic salts on the porous walls of the composite substrate. In this multifunctional composite catalytic material, transition metal oxides (Fe2O3 or CuO) serve as microwave magnetic loss control carriers, microscopically confining the local temperature field of the substrate and suppressing high-temperature thermal shear sintering of alkaline earth metal oxides. Alkaline earth oxides act as the active host for fluorine and sulfur fixation, achieving full mineralization and solidification of the fluorine and sulfur components.

[0019] Compared to existing segmented microwave processing technologies, this invention achieves disruptive innovation in three dimensions: structure, materials, and reaction mechanism, bringing four quantitative technological advantages: Architectural innovation significantly improves microwave energy utilization: Abandoning the separate structure of waveguide discharge + post-fixed bed, the multifunctional composite catalytic material of quartz discharge tube is built into the microwave strong electric field region. The microwave electromagnetic field acts on the gas phase pyrolysis and solid phase catalysis interface at the same time, and the comprehensive microwave energy utilization rate is increased from the traditional <35% to more than 65%. Achieving impedance self-matching with custom-designed SiC foam ceramics, completely eliminating thermal runaway failure: By limiting the complex permittivity and pore structure of SiC foam ceramics, TE... 10 The microwave transmission is fully transparent, and the microwave reflectivity is <1.5% under normal operating conditions, eliminating the risk of microwave source (magnetron) damage due to total microwave reflection; the transition metal oxide and SiC foam ceramic confined temperature field ensures that the macroscopic temperature of the multifunctional composite catalytic material is stable at 700-850℃, and there are no local overheating problems (>1600℃) or catalyst melting and sintering problems during continuous long-term operation. Electro-induced migration breaks through the bottleneck of lattice passivation, and the utilization rate of multifunctional composite catalytic materials is greatly improved: Electro-induced migration is generated by the high-frequency alternating electric field at the solid-gas interface, and external force drives ions to penetrate the dense CaF2 passivation layer. The effective utilization rate of multifunctional composite catalytic materials is increased from less than 40% in the existing technology to more than 90%, which greatly extends the replacement cycle of multifunctional composite catalytic materials and reduces the frequency of downtime maintenance. It exhibits excellent harmless treatment performance, achieving closed-loop disposal of greenhouse gases: SF6 single-pass degradation rate is 99.99% under standard operating conditions, and the degradation rate remains stable at ≥99.40% after 36 hours of continuous operation under 6 times concentration and high flow rate overload conditions; FTIR full-spectrum detection shows no SF6 residue, no generation of toxic fluorinated sulfur oxide byproducts such as SOF2 and SO2F2, and no greenhouse gas emissions in the exhaust gas, truly achieving harmless closed-loop treatment; Strong adaptability to working conditions: The bed gas pressure drop is ≤5kPa, which can be adapted to various industrial working conditions such as intermittent maintenance exhaust gas in substations and high-concentration sudden exhaust gas from the dismantling of scrapped electrical appliances. The equipment load has a wide adjustable range. Attached Figure Description

[0020] Figure 1 This is a schematic diagram of the structure of the electromagnetic synergistic in-situ catalytic degradation and capture device for SF6 waste gas according to the present invention; 1. Gas distribution system; 2. Three-screw tuner; 3. Rectangular waveguide; 4. Quartz discharge tube; 5. Multifunctional composite catalytic material; 6. Microwave source; Figure 2 This is the Fourier transform infrared spectrum of the exhaust gas from the system outlet of Embodiment 1 of the present invention; Figure 3 This is the Fourier transform infrared spectrum of the exhaust gas from the system outlet in Embodiment 3 of the present invention. Detailed Implementation

[0021] The following are specific embodiments of the present invention, which are described in conjunction with the accompanying drawings to further illustrate the technical solutions of the present invention. However, the present invention is not limited to these embodiments.

[0022] Example 1 Preparation of multifunctional composite catalytic materials (sol-gel impregnation method) The preparation method is as follows: Precursor sol preparation: Weigh ferric nitrate Fe(NO3)3·9H2O, calcium acetate Ca(CH3COO)2 and magnesium acetate Mg(CH3COO)2 in a molar ratio of 1:4:2 and dissolve them in a mixed solvent of anhydrous ethanol and deionized water. Add an appropriate amount of citric acid as a complexing agent and stir vigorously for 4 hours in a constant temperature water bath at 60℃ to form a transparent and uniform sol precursor with a viscosity of 12 mPa·s.

[0023] Substrate pretreatment: Select a size of Cylindrical SiC foam ceramics (88% porosity, 20 PPI pore size) measuring 40 mm × 100 mm were ultrasonically cleaned in 1 mol / L hydrochloric acid solution, acetone, and deionized water for 30 minutes, dried, and weighed using a precision electronic balance to determine their initial mass M0.

[0024] Dip-and-calcinate process: The pretreated SiC framework was vertically immersed in the sol and held for 15 minutes, then pulled out of the sol surface at a stable speed of 2 mm / s. High-pressure air was used to momentarily clear the ceramic pores, removing excess liquid and preventing pore blockage. The sample was placed in a 100℃ drying oven for 12 hours to gel, and finally transferred to a muffle furnace. Under a nitrogen atmosphere, the temperature was increased to 750℃ at a rate of 5℃ / min and calcined for 3 hours.

[0025] A dense, porous, and uniformly thick Fe2O3-CaO-MgO composite active catalytic film was coated on the pore wall surface of the SiC foam ceramic skeleton. After cooling, the total mass M1 of the coated film was weighed. The loading of the catalytic film on the SiC skeleton surface was calculated to be ω = (M1-M0) / M1×100% = 13.0% ± 0.5%.

[0026] Example 2 like Figure 1 As shown, the prepared multifunctional composite catalytic material was loaded into a high-purity quartz discharge tube with an outer diameter of 45 mm and a wall thickness of 2 mm, and the filled tube section was precisely fixed at the center of the strong electric field axis of the BJ22 rectangular waveguide.

[0027] The gas distribution system was started, and simulated electrical equipment maintenance exhaust gas was introduced. The SF6 gas flow rate was controlled at 2.0 L / h, and the auxiliary gas (argon gas flow containing 3.5 vol% water vapor) flow rate was set at 12 L / min. The microwave source was set to operate at 2.45 GHz and with a power of 800 W. Gas flow rate control is existing technology, and the components will not be described in detail here.

[0028] After microwave injection, a massive amount of diffuse, high-frequency flickering pale blue localized micro-arcs can be clearly observed through the quartz window of the rectangular waveguide: within the SiC three-dimensional mesh, a large number of arcs instantly illuminate. Dynamic tuning is performed using a three-screw tuner located at the front end of the rectangular waveguide, and the forward reflection power meter shows that the reflected power is only 12 W (reflectivity <1.5%), achieving near-perfect fluid impedance matching.

[0029] Online monitoring tests using an external infrared thermal imager showed that the macroscopic thermodynamic temperature of the quartz discharge tube skeleton remained stable at 740℃-760℃ within 95 seconds. The temperature curve remained stable during long-term operation for 6 hours, with no thermal runaway or macroscopic thermal runaway phenomena observed.

[0030] After multi-stage condensation, the exhaust gas is analyzed for composition using a Fourier transform infrared spectroscopy (FTIR) instrument. The infrared spectroscopy results show (e.g.) Figure 2 As shown): except at 1030 cm -1 In addition to the harmless non-greenhouse gas SiF4 generated by the trace reaction of free fluorine radicals with the surface of the quartz tube / ceramic framework, at 948 cm⁻¹, -1 The typical strong characteristic absorption peak of SF6 completely disappeared, and no characteristic absorption of toxic byproducts such as SO2F2 and SOF2 was observed. The single-pass continuous degradation rate of SF6 in the SF6 exhaust gas remained stable at 99.99%. Based on the principle of material balance, the highly environmentally hazardous sulfur element achieved complete gas-phase "zero escape," confirming that most of the fluorine / sulfur intermediates produced by cracking were in-situ mineralized and solidified on the multifunctional composite catalytic material by the local high-frequency electric field within the instantaneous window of the three-dimensional pore wall of the multifunctional composite catalytic material.

[0031] Example 3 This embodiment is used to verify the overload resistance of the device of the present invention in the face of a sudden influx of large flow and high concentration of SF6, as well as its continuous infrared monitoring performance of gas phase components.

[0032] The inlet flow rate of SF6 exhaust gas was significantly increased to 12.0 L / h (6 times higher than in Example 1), and the auxiliary gas flow rate was simultaneously adjusted to 25 L / min. The microwave input power was adjusted to 1500 W, and the system was operated continuously for 36 hours.

[0033] Under high-power bombardment of 1500 W, the high porosity topology of the multifunctional composite catalytic material provides a large convective heat dissipation area, rapidly establishing a dynamic equilibrium in the gas-solid forced convection heat transfer within the system. The macroscopic temperature of the porous multifunctional composite catalytic material is safely "clamped" between 810℃ and 840℃, with no temperature runaway observed during 36 hours of safe operation, and the reflected power consistently maintained at an extremely low level of ≤ 3%. During the continuous 36-hour operation, the exhaust gas was automatically scanned every 30 minutes using online gas FTIR. The infrared monitoring baseline exhibited extremely high stability during the 36-hour continuous testing. Figure 3 As shown, under continuous operation conditions with high flow and high load, the spectrum shows only weak baseline fluctuations, and the residual SF6 characteristic peak is extremely low, with SF6 at 948 cm⁻¹. -1 The characteristic peak residual absorbance remained below 0.60% (i.e., the single-pass degradation rate consistently remained above 99.40%). Throughout the long-period spectrum, no increase in absorption peaks for byproduct gases was observed, and no toxic byproducts such as sulfur fluoride or sulfur fluoride oxides were detected. This verifies the device's high-load, long-term stable processing performance and demonstrates that the alternating stress of the local micro-region electric field prevented the densification and melting of the solid surface, ensuring steady-state, harmless, in-situ capture under high-flow-rate conditions.

[0034] Example 4 Rare earth modified multifunctional composite catalytic materials In the catalytic film of Example 1, 1.5 wt% CeO2 rare earth oxide was added, and the remaining preparation parameters were the same as in Example 1; Under the same operating conditions, the macroscopic thermodynamic temperature of the quartz discharge tube filled with this multifunctional composite catalytic material stabilizes at 660℃ within 95s. The activation temperature of the multifunctional composite catalytic material drops to 660℃, and the instantaneous degradation rate of SF6 in the low-temperature range is further improved, making it suitable for low-power intermittent operation conditions.

[0035] Comparative Example 1 (Existing traditional two-stage process) The conventional industry-standard post-positioned CaO particle fixed bed + waveguide external plasma torch segmented process was adopted. The inlet parameters were the same as in Example 1: SF6 2.0 L / h, auxiliary gas 12 L / min, microwave 800 W; microwave reflectivity 22%; the highest local temperature of the fixed bed layer reached 1680℃, resulting in particle sintering; after 12 hours of continuous operation, the effective utilization rate of the packing was 37.2%, the average degradation rate of SF6 was only 82.7%, and trace amounts of SOF2 byproducts were detected in the exhaust gas.

[0036] Comparative Example 2 (Ordinary Commercial Unmodified SiC Filler) Commercially available SiC ceramics with uncontrolled dielectric parameters are directly filled into the waveguide, with other parameters the same as in Example 2; total microwave reflection occurs, the magnetron of the microwave source triggers overload protection shutdown, the filler undergoes local overheating and thermal runaway melting in a short time, and continuous operation is impossible.

[0037] Table 1

[0038] As shown in Table 1, compared to the traditional two-stage Comparative Example 1, the integrated structure of this invention achieves impedance matching through customized dielectric SiC, resulting in a significant reduction in microwave reflection and a substantial improvement in energy utilization. The alternating electric field eliminates product passivation, increasing catalyst utilization from less than 40% to over 90%, achieving a leap forward in degradation efficiency. Comparative Example 2 demonstrates that ordinary silicon carbide without dielectric and porosity optimization cannot be directly integrated into waveguides. This invention, through precise SiC parameter design, fundamentally avoids the problems of total microwave reflection and thermal runaway, solving a long-standing technical barrier in the industry.

[0039] Example 3, a long-term test with high flow rate for 36 hours, confirmed that the temperature field of the material system of the present invention is controllable, and there is no sintering failure under high power and high intake load, and the working conditions are widely adaptable.

[0040] Example 4: Rare earth doping modification can further reduce the catalytic start-up temperature, expand the applicable scenarios for low-temperature intermittent operation, and the catalytic formulation has room for optimization and expansion.

[0041] For any points not covered above, existing technologies shall apply.

[0042] Although specific embodiments of the present invention have been described in detail by way of examples, those skilled in the art should understand that the above examples are for illustrative purposes only and are not intended to limit the scope of the invention. Those skilled in the art can make various modifications or additions to the described specific embodiments or use similar methods to replace them, without departing from the direction of the invention or exceeding the scope defined by the appended claims. Those skilled in the art should understand that any modifications, equivalent substitutions, improvements, etc., made to the above embodiments based on the technical essence of the present invention should be included within the protection scope of the present invention.

Claims

1. A device for electromagnetic synergistic in-situ catalytic degradation and capture of SF6 waste gas, characterized in that: This includes the gas distribution system and the electric arc-catalytic reaction system; The arc-catalytic reaction system includes a microwave source, a three-screw tuner, a rectangular waveguide, and a quartz discharge tube that runs through the rectangular waveguide. The quartz discharge tube is filled with a multifunctional composite catalytic material within a section of the rectangular waveguide that is located in a strong electric field. The outlet of the gas distribution system is connected to one end of the quartz discharge tube. The microwaves generated by the microwave source are introduced into the rectangular waveguide by a three-screw tuner. The multifunctional composite catalytic material is a SiC foam ceramic with a composite active catalytic film coated on its surface; The composite active catalytic film comprises transition metal oxides and alkaline earth metal oxides; The complex permittivity and open-cell topology of the SiC foam ceramic are designed to match the microwaves it receives, so that the core region and the edge of the SiC foam ceramic can simultaneously generate diffuse micro-arcs and produce high temperatures. The three-dimensional open-cell topology of the SiC foam ceramic is designed to be integrated with the rectangular waveguide TE 10 Microwave-based natural electromagnetic impedance matching is achieved; the SiC foam ceramic has a three-dimensional open-cell topology with a porosity of 85%–93%, an open-cell diameter of 15–25 PPI, and a bulk density of 0.25–0.40 g / cm³. 3 ; The diameter of the quartz discharge tube is 40-50 mm, and the complex dielectric constant of the SiC foam ceramic has a real part ε′ = 8-15 and an imaginary part ε″ = 2-6.

2. The apparatus as described in claim 1, characterized in that: In the aforementioned multifunctional composite catalytic material, the loading of transition metal oxides and alkaline earth metal oxides is 10% to 25%.

3. The apparatus as claimed in claim 1, characterized in that: The transition metal oxides are Fe2O3 or CuO, and the alkaline earth metal oxides include CaO and MgO. The mass ratio of transition metal oxides to alkaline earth metal oxides is 1-2:8-9.

4. The apparatus as claimed in claim 1, characterized in that: The composite active catalytic film also includes rare earth oxides, with a loading of 0.5% to 3%.

5. The apparatus as claimed in claim 1, characterized in that: The preparation method of the multifunctional composite catalytic material is as follows: the transition metal salt and alkaline earth metal salt are dissolved in a solvent with a complexing agent and stirred in a water bath to obtain a precursor sol; the SiC foam ceramic is immersed in the above precursor sol and then taken out and the ceramic channels are blown open. Then the SiC foam ceramic is allowed to stand and gel at a certain temperature and then calcined under a nitrogen protective atmosphere.

6. The apparatus as described in claim 5, characterized in that: The complexing agent is citric acid, the water bath temperature is 60-70℃, the SiC foam ceramic is gelled at 100℃ for 12 hours, heated to 750℃ at a heating rate of 5℃ / min under nitrogen protection atmosphere, and calcined at this temperature for 3 hours.

7. The apparatus as claimed in claim 1, characterized in that: The gas distribution system is used to precisely mix SF6 waste gas and auxiliary gas source with a specific C / F molar ratio of 1:2 to 1:6 or H / F molar ratio of 1:1 to 2:1, prepare the mixed waste gas to be treated, and quantitatively deliver it to the electric arc-catalytic reaction system.

8. A method for electromagnetically synergistic in-situ catalytic degradation and capture of SF6 waste gas, characterized in that, The specific steps of using the apparatus according to any one of claims 1-7 are as follows: Start the gas distribution system and use high-purity nitrogen or argon as the purging gas to purge the inside of the quartz discharge tube; Start the gas distribution system and pass the prepared mixed waste gas containing SF6 into the quartz discharge tube; When the microwave source is turned on, continuous microwaves are injected into the rectangular waveguide. Fluorine / sulfur ions are converted into solid inorganic salts in situ under the action of the multifunctional composite catalytic material and solidified and accumulated on the porous walls of the multifunctional composite catalytic material.

Citation Information

Patent Citations

  • Supported catalyst for SF6 thermocatalytic conversion and preparation method thereof

    CN119386910A

  • Catalyst reaction method and catalyst reaction system

    JP2020038060A